Executive Compensation, Earnings Management and Over Investment in Malaysia - Ei Yet Chu,; Saw Imm Song, (Asian Academy of Management Journal of Accounting and Finance, 2012)
The study investigates the inter-relationship between executive compensation, earnings management and over investment. Using a sample of 196 Malaysian public listed firms, the findings show a positive endogenous relationship between executive compensation and over investment. Measuring equity compensation in incentive ratio, for each percent of over investment, one percent improvement in share prices will increase 23% of executive directors' equity value. Over investment, however, leads to a decline in executive directors' equity value in large shareholders controlled firms. In addition, one percent of over investment can explain 12% of earnings management. Nevertheless, earnings management does not explain executive directors' compensation. In summary, aligning over-investment with executive compensation schemes has implied that the existing compensation is insufficient for executive directors to align their interest with the objective to maximise shareholders' value.